Soil function, properties and plant diversity–biomass patterns differ between grazed and non-grazed steppe ecosystems - Mi, Jia; Wang, Qianju; Ou, Jun; Shi, Jing; Pang, Haiyan; Feng, Ziheng; Bai, Yongfei (Frontiers in Plant Science, 2025)
IntroductionGrazing and enclosure are two major grassland management techniques, which are used to preserve plant variety, productivity, and ecosystem function.MethodsIn order to compare plant diversity and ecosystem function under grazing and enclosure conditions, this study observed three typical grassland locations in southeast of Inner Mongolia via medium-scale line transect surveys.ResultsOur results showed that soil nutrients in enclosed grasslands control the diversity of plant species and aboveground biomass (AGB), which in turn regulates the amount of belowground biomass (BGB) by allocation. Enclosure consistently enhanced AGB and plant height compared to grazing, while increasing the relative contribution of perennial grasses and forbs to productivity through functional group reorganization. However, biodiversity responses were site-specific, enclosure increased plant diversity at two sites but reduced it at another, revealing landscape-dependent results.DiscussionThe grazing reshaped ecosystem regulation through three key changes: (1) the relationship between soil nutrients and AGB was inverted, and demonstrated a negative correlation between diversity and AGB, (2) established the trade-off of the effects of BGB on AGB driven by soil properties (soil nutrients and pH), (3) microbial community restructuring from dual nutrient-pH regulation to pH-dominated control and (4) grazing strengthened plant biomass-diversity linkages, while enclosure prioritized soil nutrient-plant diversity correlations. Crucially, grazing reversed the functional role of soil pH, from positive microbial community regulation in the enclosure area to negative effects, through soil microenvironment alteration. These results provided a framework in which management practices reorganize ecological networks. Enclosure strengthened soil nutrient-mediated plant-soil feedbacks, while grazing promoted pH-driven microbial selection and change of biomass allocation strategy. Meanwhile, the spatial variability of enclosure effects highlighted the importance of local environmental backgrounds for consequences of grassland management.